Cardiorespiratory fitness and cardiovascular risk factors: a study involving students in Santa Cruz do Sul, RS, Brasil - Miria Suzana Burgos; Cézane Priscila Reuter; Leandro Tibiriça Burgos; Hildegard Hedwig Pohl; Dulciane Nunes Paiva; Éboni Marília Reuter; Miriam Beatris Reckziegel; Debora Tornquist; Luciana Tornquist (Universidade de Santa Cruz do Sul, 2013)
Backgound and Objectives: The practice of physical activity and the potential benefits of cardiorespiratory fitness (CRF) should be considered as primary prevention of chronic diseases. The aim of this study was to relate CRF with risk factors causing cardiovascular diseases (obesity and hypertension) and arterial hypertension), in the municipality of Santa Cruz do Sul - RS. Method: the study of transversal character, utilized a sample of 1666 students, aged 7 - 17 years. The CRF was evaluated through the general resistance test (9 minutes); for cardiovascular risks factors, systolic and diastolic blood pressure was taken into consideration, along with anthropometric evaluations that indicate obesity, like the BMI, the sum of cutaneous flaps (ΣCF), body fat percentage (%BF), waist circumference and waist-hip ratio (WHR). Results: a high percentage of children with unsatisfactory cardiorespiratory fitness was found (70.9% for the boys and 69.4% for the girls). By comparing the CRF with cardiovascular risk factors (obesity and hypertension), it is observed that students with satisfactory cardiorespiratory fitness have better averages for BMI, WC, ΣCF,% F, SBP for both sexes, and DBP, for males. Found only a weak correlation between age (r = 0.431, p